Teacher's Strategy in Developing Children's Language Through Role Playing Activities - Putri Wijayanti; Rohinah M Noor; Ridwan Ridwan; Atika Wirdasari (Universitas Muhammadiyah Ponorogo, 2023)
The teacher's strategy is the effort or method used in delivering learning to children. Language is a form of communication both orally and in writing. The method of role playing is to portray characters or objects around the child with the aim of developing imagination (imagination). The formulation of the problem in this study is to determine macro role playing activities, to determine the language development of children aged 5-6 years and to determine language development through macro role playing activities. The type of research used in this research is qualitative descriptive qualitative. Based on the results of the research that the researchers did, the role-playing activities had been carried out in accordance with the procedures in role-playing. The steps for playing this role are in accordance with what is explained from Roestiyah's theory, namely starting from the teacher choosing the theme to be played, preparing the script or storyline, preparing the media to be used in the game, explaining the techniques and rules in the game, dividing or choosingtheir respective roles. -each child, telling while setting the first scene of discussion and evaluating learning. Therefore, the child's language development has developed very well.